Biopsychosocial determinants of financial well-being in older adults: a structural equation modeling approach - Bennetts, Chet Richard (My University, 2024)
Financial Well-Being (FWB) in older adults is a complex construct influenced by various biological, psychological, and sociological factors. This dissertation employs the Biopsychosocial (BPS) Model to examine the determinants of financial well-being among older adults using Structural Equation Modeling (SEM) techniques. Data from the Health and Retirement Study (HRS), including variables related to physical health, mental health, and social relationships, were used to explore the direct, indirect, and total effects of these factors on financial well-being. The findings reveal that the integrated BPS Model provides significant explanatory power for financial well-being beyond traditional economic models. Biological factors, such as self-reported health and chronic illness, were found to directly and indirectly influence financial outcomes. Psychological factors, including life satisfaction, depressive symptoms, and anxiety, significantly predicted financial well-being. Sociological factors, particularly the quality of social relationships, also played a crucial role, highlighting the interconnectedness of biopsychosocial determinants in shaping financial health. This research contributes to the literature by validating the BPS Model in a financial context and identifying key intervention points that can guide policy and practice aimed at improving financial well-being among older adults. The study underscores the importance of a holistic approach to financial well-being, considering the complex interplay of health, psychological resilience, and social support in later life.
Keywords: Financial well-being; Biopsychosocial Model; Structural equation modeling; Health and retirement study; Older adults